Digital Platforms and the Growth of Micro-Enterprises: Evidence from Mobile App-Based Delivery in Nepali Markets - Tamang, Min; Adhikari, Devendra (Nepal Journal of Multidisciplinary Research, 2025)
Background: In Nepal, there are several emerging mobile app-based delivery platforms that help grow micro-enterprise businesses and make the local economy vibrant. Some delivery services include Pathao, Indrive, and Yango, which deliver products from the point of origin to the customer, thus helping to sell the products. These platforms have global networks and are successfully taking the market in Nepal in the recent period. This digitalisation of the economy through digital platforms and the rise of micro-enterprising activities in the country is an emerging concept that is only limitedly discussed in the literature. Objectives: Grounded in Two-Sided Market Theory, this research aims to identify opportunities, challenges, and policy gaps while using these delivery platforms in the country. Method: This research applies a literature-review research method, reviewing literature related to journals, policies, and reports. Finding: Findings show that the use of mobile apps to find delivery vehicles and riders has increased business sales of SMEs effectively and efficiently. The SMEs have found more customers, and their business catchment has expanded. The growth of digital platforms is helpful in transforming the conventional economy toward a more virtual and advanced generation. Despite this, many customers lack digital awareness to use these apps. This intervention in the Nepali market needs to scale up with trustworthy mechanisms. Conclusion: A business ecosystem is essential, that networks four stakeholders: government oversight, mobile-app intermediary services, micro-entrepreneurs delivering products to customers, and customers. This will ensure that customers receive their desired goods through convenient and trustworthy mechanisms, promote the SMEs, and contribute to the local and national economy. Novelty of the Study: This study contributes to the limited literature on how mobile app-based delivery mechanisms support the growth of SMEs in developing nations. The application of Two-Sided Market Theory uniquely interprets how mobile apps act as intermediaries between delivery platforms and SMEs to expand their customer reach and scale their operations. This study is important for informing evidence-based policymaking to strengthen digitalisation efforts within the SME sector.